Confucianism Revisited and Transcended: The Intellectual World of Early Qing Confucian Christians—Focusing on Liu Ning and Zhang Xingyao - XIAO Qinghe (Journal of Research for Christianity in China (JRCC), 2025)
During early Qing, scholars reflected and reexamined the Confucian thoughts since late Ming. As parts of Confucians, Confucian Christians also reexamined the traditions of Confucianism. They argued that Confucianism before Qin-han dynasties was the true Confucianism; current Confucianism was not the true one; the learning of Confucius was not equal to the Confucianism. This essay tries to illustrate the Confucian Christians’ thoughts on the Confucian traditions, and how to deal with the relationship between Christianity, Buddhism and Confucianism with case studies on Liu Ning and Zhang Xingyao. According to Liu and Zhang, the Learning of Heaven was true Confucianism; conversion to the Catholicism was not to follow the teaching of barbarians but to abandon the fake Confucian and become the true Confucian; the learning of Heaven coming to the east to continue the orthodoxy of Confucius and Mencius thus restoring the Confucianism; and the learning of Heaven was really beyond of Confucianism. These thoughts are viewed as a try to find the rationality for their faith, but also as self-reflections on Confucian traditions in early Qing.